Evaluation of the Use of Electric Arc Furnace Slag and Ladle Furnace Slag in Stone Mastic Asphalt Mixes with Discarded Cellulose Fibers from the Papermaking Industry - Juan María Terrones-Saeta; Jorge Suárez-Macías; Francisco Javier Iglesias-Godino; Francisco Antonio Corpas-Iglesias (Metals, 2020)
The construction sector is one of the most demanding of raw materials that exist at present. In turn, the greenhouse gas emissions that it produces are important. Therefore, at present there are several lines of research in which industrial by-products are incorporated for the manufacture of bituminous mixtures and the reduction of CO2 emissions, framed inside the circular economy. On the base of the aforementioned, in this research, bituminous mixtures of the Stone Mastic Asphalt type were developed with electric arc furnace slag, ladle furnace slag and discarded cellulose fibers from the papermaking industry. To this end, the waste is first characterized physically and chemically, and its properties evaluated for use in bituminous mixtures. Later, different groups of samples are conformed with conventional materials and with the waste in order to be able to compare the physical and mechanical properties of the obtained bituminous mixtures. The physical tests carried out were bulk density, maximum density and void index, as well as the Marshall test for the evaluation of the strength and plastic deformations of all the bituminous mixtures manufactured. The study and evaluation of the results showed that the incorporation of slag makes it possible to absorb a greater percentage of bitumen and obtain better mechanical properties, while maintaining a similar deformation and void content. Therefore, it is feasible to use the mentioned slags to create sustainable, resistant and suitable pavements for important traffic.